COMMUNICATIVE VISUAL MEDIA-BASED SPEAKING INSTRUCTIONAL METHODS AT PEACE KAMPUNG INGGRIS PARE - Rizky Pratiwi, Widya (Fakultas Keguruan dan Ilmu Pendidikan, 2021)
Behind the problems faced in the implementation of teaching English in schools, on the contrary, learning activities in Kampung Inggris Pare are reported as having exciting and enjoyable in terms of topics and exercises they do in the classroom. The teaching methods are varied, broad, and challenging. The variation of the topics avoids boredom in the learning. Therefore, this study investigated the teaching methods conducted in this immersive environment. This qualitative study was conducted in Peace, Kampung Inggris Pare, Kediri, East Java, Indonesia. Six participants participated in this study. The data were collected through observations, interviews, documents, and visual photos. The data shows that, in teaching speaking, tutors in English Village Pare utilize a variety of media and integrated language skills, for example, by using visual media in the form of images. Five phases will be trained to achieve communicative goals in language learning, namely: pay attention to the pictures to store the concept in mind, construct the ideas about the photos (perception), regulate the way to express the ideas (mind mapping), speak up (describing the picture or anything to talk), communicative comprehension (speaking and listening session as a speaker or listener), and after review and practice the phases or activities many times, the students finally will reach the speaking fluency (ignoring filler and stuck), respect to the time, and communicative skills. This method can lead students to become successful language learners